Corrosion Study of Electroless Ni-P-W Coatings Using Electrochemical Impedance Spectroscopy - Roy,Supriyo (2012)
The present study investigates the significance of different coating process parameters on the corrosion behaviour of electrolessly deposited Ni-P-W coatings on mild steel substrate. The process parameters considered are concentration of nickel source, concentration of reducing agent, concentration of tungsten source and annealing temperature. The corrosion characteristic is evaluated by electrochemical impedance spectroscopy technique. The responses considered are charge transfer resistance and double layer capacitance. The Taguchi technique coupled with grey analysis is employed to find out the optimum combination of the process parameters for better corrosion resistance. Analysis of variance (ANOVA) reveals the contribution of the process parameters on the corrosion property of Ni-P-W coating. Finally a validation test is performed to justify the experimental result. The microstructure of the surface is studied by scanning electron microscopy (SEM); energy dispersive x-ray analysis (EDX) reveals the chemical composition and the x-ray diffraction analysis (XRD) is used to identify the phase transformation behaviour of the coating.